Man-Specific Lectins from Plants, Fungi, Algae and Cyanobacteria, as Potential Blockers for SARS-CoV, MERS-CoV and SARS-CoV-2 (COVID-19) Coronaviruses: Biomedical Perspectives - Barre, Annick (Cells, 2021)
Betacoronaviruses, responsible for the “Severe Acute Respiratory Syndrome” (SARS) and the “Middle East Respiratory Syndrome” (MERS), use the spikes protruding from the virion envelope to attach and subsequently infect the host cells. The coronavirus spike (S) proteins contain receptor binding domains (RBD), allowing the specific recognition of either the dipeptidyl peptidase CD23 (MERS-CoV) or the angiotensin-converting enzyme ACE2 (SARS-Cov, SARS-CoV-2) host cell receptors. The heavily glycosylated S protein includes both complex and high-mannose type N-glycans that are well exposed at the surface of the spikes. A detailed analysis of the carbohydrate-binding specificity of mannose-binding lectins from plants, algae, fungi, and bacteria, revealed that, depending on their origin, they preferentially recognize either complex type N-glycans, or high-mannose type N-glycans. Since both complex and high-mannose glycans substantially decorate the S proteins, mannose-specific lectins are potentially useful glycan probes for targeting the SARS-CoV, MERS-CoV, and SARS-CoV-2 virions. Mannose-binding legume lectins, like pea lectin, and monocot mannose-binding lectins, like snowdrop lectin or the algal lectin griffithsin, which specifically recognize complex N-glycans and high-mannose glycans, respectively, are particularly adapted for targeting coronaviruses. The biomedical prospects of targeting coronaviruses with mannose-specific lectins are wide-ranging including detection, immobilization, prevention, and control of coronavirus infection.